If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -2p = 4p + -4 Reorder the terms: 20 + -2p = -4 + 4p Solving 20 + -2p = -4 + 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. 20 + -2p + -4p = -4 + 4p + -4p Combine like terms: -2p + -4p = -6p 20 + -6p = -4 + 4p + -4p Combine like terms: 4p + -4p = 0 20 + -6p = -4 + 0 20 + -6p = -4 Add '-20' to each side of the equation. 20 + -20 + -6p = -4 + -20 Combine like terms: 20 + -20 = 0 0 + -6p = -4 + -20 -6p = -4 + -20 Combine like terms: -4 + -20 = -24 -6p = -24 Divide each side by '-6'. p = 4 Simplifying p = 4
| -48/-3= | | -3(3p+4)-2(4-11p)=3(2+4p) | | 2x^2+12x=4 | | d=1/2(3)-2 | | 7(4-3x)+3=-6(x-4)-8 | | -48/3= | | b^2-3b+4=0 | | 59-4=91 | | 8n+6-6n=34 | | 4*(3-6a)=36 | | x^2+12x-6=46 | | 15x^2-19x-10= | | 4y=-36+4x | | (2x+2)+y+7=180 | | 2(r-.5)=-2 | | 144p-309.60=50.40 | | (r-2)(r+8)=23 | | 18-7x+1=-9 | | 4f=-7 | | 6(2/5)-3= | | 63-6x=1x | | -2(.5-4s)=-3(4-3.5s) | | 2x=14+y | | -(2+7x)-6(-7-x)=36 | | -3x+4=-11 | | -11.77+11.6b=19.43+13.9b+2.5b | | 2x^2+3x+6=13 | | -7(-1)= | | 11-3a=10 | | x-5y=25 | | 60x^2+3xy-36y^2=0 | | 1.4x+1.2y-3.8=-9 |